Psychoanalytical study of Sarah Kane, a feminist writer and her power of language, in “Crave” - Kamarzadeh, Sepideh (Revista Hipótese, 2016)
In this study attempts is made to study treats of characters within a play and analyze it through Freud's theories and the play's relationship with expressionist theater and experimental theater. Sarah Kane was a British author, who committed suicide at age 28. Obviously, this play is full of loss, death, unfulfilled desire, rape, violence, so this essay surveys the play, analyzes through Freud's theory of psychosexual development and efforts to find any relationship between Sarah Kane's Crave and Freud's psychosexual development theory.
Keywords: Sigmund Freud; Sarah Kane; psychoanalytic development; Crave; life and death instincts